2011
DOI: 10.1051/0004-6361/201116828
|View full text |Cite
|
Sign up to set email alerts
|

The interstellar cosmic-ray electron spectrum from synchrotron radiation and direct measurements

Abstract: Aims. We exploit synchrotron radiation to constrain the low-energy interstellar electron spectrum, using various radio surveys and connecting with electron data from Fermi-LAT and other experiments. Methods. The GALPROP programme for cosmic-ray propagation, gamma-ray and synchrotron radiation is used. Secondary electrons and positrons are included. Propagation models based on cosmic-ray and gamma-ray data are tested against synchrotron data from 22 MHz to 94 GHz. Results. The synchrotron data confirm the need … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
249
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(284 citation statements)
references
References 70 publications
30
249
4
1
Order By: Relevance
“…The Galactic synchrotron spectrum curves significantly below a few GHz (e.g., de Oliveira-Costa et al 2008;Strong et al 2011). To generate a useful spectral constraint from just one low-frequency map, we cannot afford to fit this curvature independently at each pixel, as otherwise the low-frequency point would always fit perfectly and give no constraint on the highfrequency spectrum; instead we force the curvature to be constant across the sky, and we have tried several approaches to regularize the fit.…”
Section: Synchrotronmentioning
confidence: 99%
See 2 more Smart Citations
“…The Galactic synchrotron spectrum curves significantly below a few GHz (e.g., de Oliveira-Costa et al 2008;Strong et al 2011). To generate a useful spectral constraint from just one low-frequency map, we cannot afford to fit this curvature independently at each pixel, as otherwise the low-frequency point would always fit perfectly and give no constraint on the highfrequency spectrum; instead we force the curvature to be constant across the sky, and we have tried several approaches to regularize the fit.…”
Section: Synchrotronmentioning
confidence: 99%
“…As expected, simple power-law fits are inconsistent with our data, generating large and spurious "gain corrections" at 408 MHz. Strong et al (2011) and Orlando & Strong (2013) model the observed synchrotron emission for given Galactic magnetic Fig. 15.…”
Section: Synchrotronmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, advances in computing now enable us to solve the diffusion energy loss equation via approximation rather than analytical modelling. While analytical solutions for simple cases can give insight into the relations between the quantities involved and are good for rough estimates, they can become so complicated that no insight is gained (Strong et al 2011). On the other hand, numerical models are intuitive because they are able to generate the cosmic ray distribution over the galaxy for all species, the best example being the Galactic Propagation (GALPROP) code .…”
Section: Introductionmentioning
confidence: 99%
“…While our own Galaxy has been modelled extensively using the GALPROP code, including recent work using the observed synchrotron spectral index to constrain the parameters governing CRE propagation (Strong et al 2011), external galaxies have not been modelled with both diffusion and energy losses of CREs since Segalovitz (1977;M 51), Strong (1978;NGC 891), and Pohl & Schlickeiser (1990;NGC 4631). Additionally, these were analytical models.…”
Section: Introductionmentioning
confidence: 99%